Pengaruh waktu perkawinan pasca beranak terhadap performa produktivitas sapi induk pada kondisi peternakan rakyat - Lukman Affandhy; D. M. Dikman; D. Ratnawati (Faculty of Animal Science, Universitas Brawijaya, 2019)
The mating of the beef cow is important factors in beef cattle breeding. The research aims to obtain the mating time of the cow after calving in smallholder farmers. The study was conducted on Pasuruan and Probolinggo Regency, East Java Province. Observations were on productivities performance in Ongole-cross breed cows in smallholder farmers from 2010 to 2013. The study used a randomized block design with four treatment groups postpartum mating, namely Group I (<60 days), Group II (60-<90 days), Group III (90-<120 days), and Group IV (>120 days. The parameters measured included postpartum anoestrus interval/PPAI, service per conception (S/C), conception rate (CR), calf weaning time, and calving interval/CI, percentage of calf birth and death. Data were analyzed using ANOVA; followed by the Duncan test using SPSS. The values of PPAI in PO cows showed very significant differences (P<0.01) between the mating time groups. Calving Interval in group IV showed the highest value of 499.0±123.4 days (P <0.05) compared with group I, II, III. The highest CR value was in group III (79.45%) than I, II and IV. The highest calf mortality was in the group I (16.67%) than in group II, III and IV. The percentage of calf births in groups I, II, III, and IV are the same, but the lowest calf weaning time of obtained in group II mating was 92.8±22.5 (P<0.01) than group I, III and IV. In conclusion, the most efficient mating time was 60-<90 days after calving.